Long-Term Intrahost Evolution of Staphylococcus aureus Among Diabetic Patients With Foot Infections - Lavigne, Jean-Philippe; Hosny, Michel; Dunyach-Remy, Catherine; Boutet-Dubois, Adeline; Schuldiner, Sophie; Cellier, Nicolas; Yahiaoui-Martinez, Alex; Molle, Virginie; La Scola, Bernard; Marchandin, Hélène; Sotto, Albert (Frontiers in Microbiology, 2021)
Staphylococcus aureus is one of the main pathogens isolated from diabetic foot infections (DFI). The purpose of this study was to evaluate the importance of the persistence of S. aureus in this environment and the possible modifications of the bacterial genome content over time. Molecular typing of S. aureus isolates cultured from patients with the same DFI over a 7-year study revealed a 25% rate of persistence of this species in 48 patients, with a short median persistence time of 12 weeks (range: 4 to 52 weeks). Non-specific clonal complexes were linked to this persistence. During the follow-up, bla genes were acquired in three cases whereas some virulence markers were lost in all cases after a long period of colonization (21.5 weeks). Only one patient (2%) had a long-term persistence of 48 weeks. The genome sequencing of a clonal pair of early/late strains isolated in this patient showed mutations in genes encoding bacterial defence and two-component signal transduction systems. Although this study suggests that the long-term persistence of S. aureus in DFI is a rare event, genomic evolution is observed highlighting the low adaptive ability of S. aureus to the specific environment and stressful conditions of diabetic foot ulcers. These results provide the basis for better understanding of S. aureus dynamics during persistent colonization in chronic wounds.